Remnant cholesterol is an independent determinant of the presence and extent of subclinical carotid atherosclerosis in statin-naive individuals. (14th October 2021) - Delialis, D; Aivalioti, E; Mavraganis, G; Dimopoulou, A M; Sianis, A; Angelidakis, L; Patras, R; Petropoulos, I; Ioannou, S; Syrigou, R; Kanakakis, J; Georgiopoulos, G; et al.
Abstract: Background: Despite continuous improvements of diagnostic and therapeutic algorithms for cardiovascular disease (CVD), mortality from CVD remains high suggesting unaddressed residual risk. Remnant cholesterol (RC) consists the cholesterol content of triglyceride-rich lipoproteins, which along with LDL cholesterol infiltrate the arterial wall, accumulate and cause atherosclerosis. Increased remnant cholesterol (RC) levels have been previously associated with future adverse cardiac events despite hypolipidemic therapy. However, a mechanistic association of RC levels with human atherosclerosis in vivo has not been proven in a clinical setting. Purpose: To evaluate the association of RC levels with the presence and extend of subclinical carotid atherosclerosis. Methods: In this retrospective cohort study, 438 subjects from the Athens Vascular Registry without clinically overt CVD or treatment with statin were recruited. Atherosclerotic burden was assessed by B-mode carotid ultrasonography using: 1. Maximal carotid wall thickness [maxWT, the highest intima-media thickness (IMT) or highest atherosclerotic plaque thickness (PLQ) if present derived from all carotid sites], 2. Total thickness (sumWT, sum of maximal wall thickness), 3) high plaque burden (PLQ ≥2) and 4) average carotid IMT (avgIMT). RC was calculated using the formula RC=total cholesterol-LDL-C-HDL-C. Results: Mean (SD) age was 54.8±12.4 years old with 41% being males. Subjects with RC>median (=18mg/dl) had higher sumWT (6.12±0.7 vs 5.57±1.7, p=0.002), maxWT (1.61±0.7 vs 1.43±0.7, p=0.008) and avgIMT (0.88±0.16 vs 0.83±0.16, p=0.003) vs RC<median.>median was associated with higher odds for increased sumWT (highest tertile, OR: 2.15 95% CI 1.26–3.66, p=0.006) and maxWT (OR: 2.15 95% CI: 1.38–3.33, p=0.001), and a higher plaque burden (≥2 plaques, OR: 2.1 95% CI 1.93–3.1, p<0.001) after adjustment for age, gender and systolic blood pressure, glomerular filtration rate, smoking, diabetes mellitus, body mass index and LDL-C Conclusion: In a statin-naive population without clinically overt CVD, increased RC levels were associated with the presence and extend of subclinical carotid atherosclerosis. These findings provide novel mechanistic insight into mechanisms associated with increased CVD risk in individuals with high RC levels. Funding Acknowledgement: Type of funding sources: None.